Sistem Pengontrol Lampu Smart Home Berbasis Android dengan Arduino Uno dan Relay 5V - Widya Ari Rizki; Rahmadani Fitri Pjt; Raja Syahmuda Siregar; Juniar Hadianti; Dicky Apdilah (Lembaga Pengembangan Kinerja Dosen, 2026)
The rapid development of technology has encouraged the creation of automated systems to improve efficiency and convenience in daily life, especially in controlling electrical devices. This study aims to design and implement a smart home light control system based on Android using Arduino Uno and a 5V relay, with Bluetooth communication as the interface between the smartphone and the microcontroller. The research method includes hardware design, software development, and system testing. The system was tested for its ability to receive ON and OFF commands from the Android application, the responsiveness of the relay, and the stability of Bluetooth communication within a range of approximately 10 meters. The results show that the system can control the lamp effectively and reliably, with fast response time and minimal communication errors. This implementation demonstrates a practical, low-cost solution for home automation, providing convenience, energy efficiency, and flexibility for users. The findings suggest that such systems can be further developed to include multiple lamps or integrated with IoT networks for enhanced smart home applications.